Peak Oil and the Everyday Complexity of Human Progress Narratives - Pruit, John (Narrative Works, 2012)
The “big” story of human progress has polarizing tendencies featuring the binary options of progress or decline. I consider human progress narratives in the context of everyday life. Analysis of the “little” stories from two narrative environments focusing on peak oil offers a more complex picture of the meaning and contours of the narrative. I consider the impact of differential blog site commitments to peak oil perspectives and identify five narrative types culled from two narrative dimensions. I argue that the lived experience complicates human progress narratives, which is no longer an either/or proposition